An analysis of slang language used in raditya dika’s podcast - Delpia, Fila; Pasaribu, Tiara k.; Sembiring, Rony Arahta (Journal of English Language and Education, 2024)
Language is the most important means of communication in life, whether in the form of writing, orally, or only in the form of certain signs. Without language, humans cannot socialize with other people and slang is a phenomenon of the use of linguistic variations that are formed as a result of language development and social dynamics in society. Slang is a new vocabulary owned by a certain group of people that is related to informal conversations and used in informal situations. This research aims to find out the types and meanings of slang contained in Raditya Dika's podcast. The data source for this research was taken from Raditya Dika's podcast which was uploaded to his Spotify account with the title "Guide to Facing Haters ft Uus". This research uses a qualitative descriptive method and data is collected by transcribing conversations from Raditya Dika and Uus. 23 pieces of data were found in Raditya Dika's podcast related to slang language. The research results show that the Podcast "Guide to Facing Haters ft Uus" by Raditya Dika contains 5 types of slang according to the theory of Allan and Burridge (2006), namely Fresh and Creative, Flippant, Imitative, Acronym, and Clipping. From the research results, it was found that the Fresh and Creative types were most widely used with 10 data, 8 data for Acronyms, 3 data for Imitative, 1 data for Flippant, and 1 data for Clipping.